PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPA SISWA KELAS IV MI AL-IKHLAS - Misra, Misra; Selvi, Nurhayati; Alannasir, Wahyullah (ALENA : Journal of Elementary Education, 2023)
This study aims to determine the effect of student learning outcomes before being given treatment (Treatment) and after being given treatment (Treatment) during the Posttest and to find out the learning model of Project Bsed Learning can improve student learning outcomes in Natural Sciences (IPA) subjects for class students. IV MI AL-Ikhlas Buntu Podong, Masalle District, Enrekang Regency. The method used in this study is an experimental method, the design used is an experimental research design (Pre-Experimental) with the type of research One Group Pretest-Posttest. The description of the implementation of the Project Based Learning learning model for class students has been carried out face-to-face which is carried out in very good categories. Student learning outcomes using the Project Based Learning learning model, namely the average score in the posttest is higher with an average score of 84.44 compared to the pretest score with an average learning result of 66.11. So there is a significant increase in the average value of learning outcomes, namely 18.33 with a percentage of 27%. The use of the Project Based Learning learning model has an effect on student learning outcomes. This can be seen from the hypothesis test or independent sample T-Test obtained 0.000 so that the value is 0.000 <0.05. It is known that there is a significant influence on the learning outcomes of Natural Sciences (IPA) for fourth grade students of MI AL-Ikhlas Buntu Podong, Masalle District, Enrekang Regency.